The Policy of Pro-Bebaya in Improving the Welfare of the Community in the Samarinda City - Hariati Hariati; Dini Zulfiani; Annisa Saskia Saputri; Ahsari Janur Framitha (Program Pascasarjana Universitas Negeri Makassar, 2023)
This research aims to describe the policy of the Community Development and Empowerment Program (Program Permbangunan dan Pemberdayaan / Pro-bebaya) in Enhancing the Welfare of the Community in the City of Samarinda. This research method employs descriptive qualitative research to provide an impartial explanation of specific conditions. Primary data for this research was obtained through observation, in-depth interviews, and documentation, while secondary data, obtained through literature reviews and relevant written records related to the subject, was used to support the primary data. The research results indicate that the implementation of the Community Development and Empowerment Program (Probebaya) in Enhancing the Welfare of the Community in the City of Samarinda, as observed in the field research process, including infrastructure development, economic development, social and cultural activities, health-related activities, education-related activities, and youth-related activities, has been carried out effectively. This is evidenced by the fact that the residents in the Air Hitam Subdistrict have experienced the benefits of the Probebaya program, although there are some inhibiting and supporting factors in the program's implementation.